Humanities and Big Data in Ibero-America : Theory, Methodology and Practical Applications - Ana Gallego Cuiñas; Daniel Torres-Salinas (De Gruyter, 2023)
This volume presents the first comprehensive study on the relationship between the Human Sciences and Big Data, with special emphasis on the Ibero-American space. The volume is divided into three parts (theoretical, methodological and practical) with an interdisciplinary vision that integrates thought, culture, language, literature, theoretical criticism, society or the use of new bibliometric techniques.